Adobe Illustrator 10. - Adobe Systems (San Jose (Calif.) : Adobe, 2002)
1.Getting to know the work area 2.Creating basic shapes 3.Painting 4.Drawing with the pen tool 5.Working with brushes 6.Transforming objects 7.Working with type 8.Blending shapes and colors 9.Using appearance attributes, styles and effects 10.Working with layers 11.Creating airbrush effects 12.Drawing cylinders and boxes 13.Printing artwork and producing color separations 14.Combining illustrator graphic and photoshop images 15.Creating a web publication
Includes index.
"The official training workbook developed by the staff of Adobe"--Cover.
Keywords: Adobe Illustrator (Computer file).; Computer graphics; Illustrators